Gas and Water Seepage of Tight Gas and Its Application in Well Production Analysis - Rui Zhang; Yang Gao; Yanbin Zhang; Peng Zhang; Xiaoli Pan; Wenjing Yang; Ligang Lv; Xingguan Chen (Geofluids)
Changqing tight gas field has been on fashion among China in recent years. Figuring out gas and water seepage behaviors matters a lot for maximizing gas reservoir recovery. One tool for that is to conduct two-phase seepage experiment and reveal seepage features. Experiments show that gas or water’s flowing capacity has a directly positive relationship with its saturation. The larger saturation, the higher permeability. Thus, one method of determining whether a gas well produces water or not is to compare the initial water saturation with its starting-flowing saturation. If the initial gas or water saturation is larger than its critical saturation, it starts to flow. Meanwhile, this critical saturation ranges hugely. For reservoirs with high porosity, permeability, and pore structure like type I, the starting-flowing saturation is 15.6% for gas and 36.6% for water, meaning that it is easily for gas or water to reach the critical saturation and make the seepage happen. The critical saturation in reservoir of type III which has low porosity, permeability, and pore structure is as high as 28.8% for gas and 58.1% for water, indicating that high fluid saturation is needed to have it flow. Finally, four horizontal wells in Sudongnan block are analyzed to verify the method. The prediction that two of them will produce water in the beginning and the other two will not is highly in line with their production data. This method has been proved effective in the prediction of gas wells.